PENGARUH PERILAKU KONSUMEN DAN KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BUSANA MUSLIMAH PADA ONLINE SHOP - sherly novita; Efni Anita; Novi Mubyarto; Munsarida Munsarida (Program Studi Manajemen Keuangan Syariah, 2022)
This study aims to determine the effect of consumer behavior and consumer satisfaction on purchasing decisions. This study uses quantitative methods and the type of data used is primary data, which is obtained from the results of distributing online questionnaires to respondents. These results can be seen partially. (T test) between Consumer Behavior and Consumer Satisfaction with Purchase Decision shows the value of tcount 4.107 > ttable 1.986. Between Consumer Satisfaction with Purchase Decision shows the value of tcount 5,208 < ttable 1,986. Simultaneously, this is evidenced by the results of fcount of 32,000>ftable with a significant value (sig) of 0.000. Because the sig value is much smaller than 0.05, the regression model can be used to predict that consumer behavior and consumer satisfaction simultaneously affect purchasing decisions. While the most dominant variable influencing purchasing decisions is customer satisfaction with a significant value obtained of 0.000 <0.05